The Craft of Christ's Imperfect Tailors - Coalter, Milton J. (Theology today, 1993)
“Once knowledge becomes habitual, one can act to recall its content, without constantly referring to recorded sources previously read. A ‘studied response’ in ministry takes on new meaning when viewed in the light of the medieval scholar's concern to create an internal book of memory. Knowledge derived from reading and study, but stored in a constantly ruminating memory, presents the promising potential of rapid, yet thoughtful, responses to spontaneous occasions for ministry and service.”